THE INTERPRETATION OF MENTAL HEALTH ROMANTICIZED IN THE LYRICS OF THE SONG “RAYUAN PEREMPUAN GILA” BY NADIN AMIZAH - Azahra, Sarmila; Priyoto, Priyoto; Mashuri, Mashuri (Jurnal Review Pendidikan dan Pengajaran, 2024)
Song is a medium that can be used to convey messages to many people. The song aims to understand and reveal the overall meaning contained in the song lyrics as a whole. The purpose of this research is to find out the semiotic romanticized lyrics in “Rayuan Perempuan Gila” related to mental health. To analyze this song the writer uses the formulation of the semiotic model of Roland Barthes, where the analysis of this study emphasizes the search for denotations, connotations, and mythical meanings through the refinement of the expressions lyrical and visual. This study used a qualitative method of research that is descriptive and tends to use analysis. The song also carries the message that support, understanding and efforts to understand people with mental problems are very important.. The results of the research show that a). Emotional and thinking b). Loving yourself is not easy c). Anxiety and awareness.